A quantitative tour of the social sciences - Gelman, Andrew; Cortina, Jeronimo (Cambridge University Press, 2009)
This overview gives an accessible, non-technical sense of how quantitative research is done in the social sciences. Upon finishing this book, the reader should have a sense of the different models and different ways of thinking in economics, history, sociology, political science and psychology.